Isotopic footprint: ¿does the forensic analyses improve forest control? - Melessa, Ulrich (2013)
In the Ecuadorian market a high percentage of timber from tropical forests is of illegal origin. Illegal acts and infringments along the production chain are more frequent if the concern species is valuable such as mahogany (Swietenia macrophylla) and cedar (Cedrela odorata). In this regard, one of the most frequently falsified data is the geographical origin of wood. At date there is no forensic scientific method for determining objectively and independently the geographic source stated in the documentation of traded timber. The analysis of the isotope composition, known as a isotope fingerprint, has a clear special pattern and is feasible for this purpose.From Ecuador samples of mahogany and cedar were contributed to build a geo-referenced database and improve the method to make it more operational to serve in control and surveillance programs. This article explains the problems related to the subject, the method and its potential use.